2022
DOI: 10.1371/journal.pone.0260078
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of non-Hodgkin’s lymphoma among adults in Sardinia, Italy

Abstract: The causes of the peculiar time trend in the incidence of non-Hodgkin’s lymphoma (NHL) in most parts of the world and of its geographic distribution are still unknown. We used the data base of 1974–2003 incident cases of hematological malignancies to explore the time trend of NHL incidence in the region of Sardinia, Italy, and we used Bayesian methods to plot the probability of NHL incidence by residential unit on the regional map. In 1974–2003, 4109 NHL cases were diagnosed among resident adults in Sardinia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
0
7
2
Order By: Relevance
“…The 1974-2003 NHL age- and gender-adjusted incidence rate among the Sardinian adult population (aged 25 years or more) was 13.4 per 100,000 (95% CI 13.0 – 13.8) [29], ranging from 0 to 27.9 across the 356 communes. The 2020 cumulative incidence of COVID-19 was 2,117 per 100,000 population, ranging from 0 in four communes with 77, 148, 224, and 506 residents, respectively, to 11,935 in a commune with 1,240 residents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1974-2003 NHL age- and gender-adjusted incidence rate among the Sardinian adult population (aged 25 years or more) was 13.4 per 100,000 (95% CI 13.0 – 13.8) [29], ranging from 0 to 27.9 across the 356 communes. The 2020 cumulative incidence of COVID-19 was 2,117 per 100,000 population, ranging from 0 in four communes with 77, 148, 224, and 506 residents, respectively, to 11,935 in a commune with 1,240 residents.…”
Section: Resultsmentioning
confidence: 99%
“…The age- and gender-standardized incidence rates of NHL between 1974-2003 were available for all the 356 autonomous administrative units (communes) in Sardinia as of 1974 [29]. Briefly, due to the lack of a regional Cancer Registry, the chief haematologist of the Cagliari Oncology Hospital, with the support of the health authorities and the clinical departments of the whole region, created a database of all incident haematological cancers, diagnosed among the Sardinian population of both genders and any age from 1974-2003 [30].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The age-and gender-standardized incidence rates of NHL between 1974-2003 were available for all the 356 autonomous administrative units (communes) in Sardinia as of 1974 [30]. Briefly, due to the lack of a regional Cancer Registry, the chief haematologist of the Cagliari Oncology Hospital, with the support of the health authorities and the clinical departments of the whole region, created and regularly updated a database by prospectively registering all incident haematological cancers diagnosed among the Sardinian population of both genders and any age from 1974-2003 [31].…”
Section: Methodsmentioning
confidence: 99%
“…A recently published Bayesian analysis showed that, over the three decades between 1974 and 2003, the NHL incidence tended to cluster in the north-eastern part of the Italian region of Sardinia and its major urban centre, with the low incidence areas located in the south [30]. The ecological analysis did not identify plausible explanatory factors among the conditions known to increase NHL risk.…”
Section: Introductionmentioning
confidence: 95%